Development and validation of a sensitive liquid‐chromatography tandem mass spectrometry assay for mycophenolic acid and metabolites in HepaRG cell culture: Characterization of metabolism interactions between p‐cresol and mycophenolic acid. (6th May 2019) - Rong, Yan; Kiang, Tony K.L.
Abstract: Mycophenolic acid (MPA), a frequently used immunosuppressant, exhibits large inter‐patient pharmacokinetic variability. This study (a) developed and validated a sensitive liquid chromatography–tandem mass spectrometry (LC–MS/MS) assay for MPA and metabolites [MPA glucuronide (MPAG) and acyl‐glucuronide (AcMPAG)] in the culture medium of HepaRG cells; and (b) characterized the metabolism interaction between MPA and p ‐cresol (a common uremic toxin) in this in vitro model as a potential mechanism of pharmacokinetic variability. Chromatographic separation was achieved with a C18 column (4.6 × 250 mm, 5 μm) using a gradient elution with water and methanol (with 0.1% formic acid and 2 mm ammonium acetate). A dual ion source ionization mode with positive multiple reaction monitoring was utilized. Multiple reaction monitoring mass transitions ( m / z ) were: MPA (320.95 → 207.05), MPAG (514.10 → 303.20) and AcMPAG (514.10 → 207.05). MPA‐d3 (323.95 → 210.15) and MPAG‐d3 (517.00 → 306.10) were utilized as internal standards. The calibration curves were linear from 0.00467 to 3.2 μg/mL for MPA/MPAG and from 0.00467 to 0.1 μg/mL for AcMPAG. The assay was validated based on industry standards. p ‐Cresol inhibited MPA glucuronidation (IC50 ≈ 55 μm ) and increased MPA concentration (up to >2‐fold) at physiologically relevant substrate‐inhibitor concentrations ( n  = 3). Our findings suggested that fluctuations in p ‐cresol concentrations might be in part responsible for the large pharmacokinetic variability observed for MPA in the clinic.